2017
DOI: 10.1186/s12884-017-1380-y
|View full text |Cite
|
Sign up to set email alerts
|

A case of acute Sheehan’s syndrome and literature review: a rare but life-threatening complication of postpartum hemorrhage

Abstract: BackgroundSheehan’s syndrome occurs because of severe postpartum hemorrhage causing ischemic pituitary necrosis. Sheehan’s syndrome is a well-known condition that is generally diagnosed several years postpartum. However, acute Sheehan’s syndrome is rare, and clinicians have little exposure to it. It can be life-threatening. There have been no reviews of acute Sheehan’s syndrome and no reports of successful pregnancies after acute Sheehan’s syndrome. We present such a case, and to understand this rare condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 25 publications
(43 reference statements)
1
41
2
3
Order By: Relevance
“…[1][2][3] Severe PPH is an obstetric emergency that occurs in 1% to 2% of live births and accounts for approximately 140,000 maternal deaths annually worldwide. 4 Treatment strategies include pharmacological measures (eg, oxytocin administration), intrauterine tamponade (eg, Bakri balloon or Sengstaken-Blakemore tube), uterine artery ligation, hysterectomy, uterine compression sutures, and uterine artery embolization (UAE). [5][6][7][8][9][10][11][12] A few publications have shown higher rates of preterm birth, fetal growth restriction (FGR), and placenta accreta spectrum (PAS) among women who became pregnant after UAE for PPH.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Severe PPH is an obstetric emergency that occurs in 1% to 2% of live births and accounts for approximately 140,000 maternal deaths annually worldwide. 4 Treatment strategies include pharmacological measures (eg, oxytocin administration), intrauterine tamponade (eg, Bakri balloon or Sengstaken-Blakemore tube), uterine artery ligation, hysterectomy, uterine compression sutures, and uterine artery embolization (UAE). [5][6][7][8][9][10][11][12] A few publications have shown higher rates of preterm birth, fetal growth restriction (FGR), and placenta accreta spectrum (PAS) among women who became pregnant after UAE for PPH.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, acute presentation of SS, although rare, can also occur and has been associated with life-threatening complications. 22 Finally, unremitting headache in the early postpartum period can be an initial presentation of SS and should be considered in the differential diagnosis. When the headache workup is negative, serial brain MR may be indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Matsuzaki and colleagues compiled 21 cases of acute Sheehan's syndrome from the literature (1990-2014) and included his own rare case of a successful second pregnancy after induction of ovulation in a patient with Sheehan's syndrome under replacement treatment with hydrocortisone and thyroxine (Table 1 describes only his case). The authors reported variable onset of symptoms of different pituitary hormonal deficiencies with a median time of presentation of secondary AI being 7.9 days following delivery (29).…”
Section: Lactation In the Context Of Aimentioning
confidence: 99%
“…To ensure evaluation of cases in the context of modern treatment, only cases dating 1976 onward were considered for inclusion (8,20,26,27,28,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52). This search identified 28 cases of primary AI, a case series with 17 cases of treated adrenocortical carcinoma patients, out of which 7 were included as they were on hydrocortisone treatment following surgical treatment (51) PAI (5) Y (2/5)…”
Section: Fertility and Preconceptional Considerationsmentioning
confidence: 99%